The Uniting Church in Australia - Bentley, Peter, 1961-; Hughes, Philip J.; Australia. Bureau of Immigration, Multicultural and Population Research (Canberra : Australian Govt. Pub. Service, 1996)
A description of the creation of the Uniting Church within an Australian context and the traditions which came together as the Uniting Church. It outlines the doctrines, practices and organisation which have developed and it examines the church in light of the data in the 1991 Australian census.
Cover: Bureau of Immigration, Multicultural and Population Research.
Keywords: Uniting Church in Australia -- History